Clinical application of a rapid cervical cancer screening method: Folate receptor–mediated staining of cervical neoplastic epithelia. Issue 1 (14th October 2016) - LI, Donghong; Chen, Lihong; Wang, Huifang; Yang, Hongli; Dai, Yuping; Yu, Cuige; Dong, Yun
Abstract: Aim: A newly developed cervical cancer screening method – folate receptor–mediated epithelium staining utilizes methylene blue internalized by folate receptor–mediated endocytosis to stain cervical intra‐epithelial neoplasia. We test the clinical feasibility of this method in this study. Methods: A total of 14 344 women who were at least 21 years old and had been sexually active, participated in the study. In gynecological clinics, participants underwent cervical cancer screening with folate receptor–mediated epithelium staining followed by cytology sampling. The color change of methylene blue in the cervical neoplastic epithelium can then be detected by the cotton swabs placed inside the cervix. A change of color to blue, bluish black or black is positive, whereas a change of color to green or no color change indicates negative result. Three hundred and twenty‐three women who were positive with either or both tests had histopathologic diagnosis. Results: The sensitivity, specificity, positive predictive value and negative predictive value of folate receptor–mediated epithelium staining for cervical intra‐epithelial neoplasia grade 2 and worse was 85.7%, 76.4%, 61.3% and 92.5%, respectively. Folate receptor–mediated epithelium staining had moderate agreement with cytology thresholded at atypical squamous cells, unable to exclude a high grade intra‐epithelial lesion and was more sensitive that the later (85.7% vs 74.5% for intra‐epithelial neoplasia grade 2 and worse; 89.2% vs 75.4% for intra‐epithelial neoplasia grade 3 and worse). Conclusion: Folate receptor‐mediated epithelium staining is capable of detecting cervical precancerous and cancerous lesions rapidly and cost‐effectively.